Pharmacokinetics and Safety of Mitragynine in Beagle Dogs - Maxwell, Elizabeth A.; King, Tamara I.; Kamble, Shyam H.; Raju, Kanumuri Siva Rama; Berthold, Erin C.; León, Francisco; Avery, Bonnie A.; McMahon, Lance R.; McCurdy, Christopher R.; Sharma, Abhisheak (Planta Medica, 2020)
Mitragynine is the most abundant psychoactive alkaloid derived from the leaves of Mitragyna speciosa (kratom), a tropical plant indigenous to regions of Southeast Asia. Mitragynine displays a moderate affinity to opioid receptors, and kratom is often self-prescribed to treat pain and/or opioid addiction. The purpose of this study was to investigate the safety and pharmacokinetic properties of mitragynine in the dog. Single dose oral (5 mg/kg) and intravenous (0.1 mg/kg) pharmacokinetic studies of mitragynine were performed in female beagle dogs. The plasma concentrations of mitragynine were measured using ultra-performance liquid chromatography coupled with a tandem mass spectrometer, and the pharmacokinetic properties were analyzed using non-compartmental analysis. Following intravenous administration, mitragynine showed a large volume of distribution (Vd, 6.3 ± 0.6 L/kg) and high clearance (Cl, 1.8 ± 0.4 L/h/kg). Following oral mitragynine dosing, first peak plasma (Cmax, 278.0 ± 47.4 ng/mL) concentrations were observed within 0.5 h. A potent mu-opioid receptor agonist and active metabolite of mitragynine, 7-hydroxymitragynine, was also observed with a Cmax of 31.5 ± 3.3 ng/mL and a Tmax of 1.7 ± 0.6 h in orally dosed dogs while its plasma concentrations were below the lower limit of quantification (1 ng/mL) for the intravenous study. The absolute oral bioavailability of mitragynine was 69.6%. Administration of mitragynine was well tolerated, although mild sedation and anxiolytic effects were observed. These results provide the first detailed pharmacokinetic information for mitragynine in a non-rodent species (the dog) and therefore also provide significant information for allometric scaling and dose predictions when designing clinical studies.
Keywords: mitragynine; 7-hydroxymitragynine; absolute bioavailability; pharmacokinetics; kratom; Mitragyna speciosa; Rubiaceae